Dose regular physical activity improve the relationships among self-efficacy, resilience, happiness, and well-being in youth people with hearing disability in Guangdong—a moderation model - Zhan, Wenpeng (Frontiers in Psychology, 2025)
This study aims to explore the relationships among self-efficacy, resilience, happiness, and well-being in youth with hearing disabilities while also investigating the moderating effects of regular physical activity. The research used a quantitative method, random sampling was used to select 10 universities with disability support programs and purposive sampling was used to recruit eligible respondents. A total of 332 eligible respondents, university students diagnosed with moderate or greater hearing impairment, were included. Data analysis was conducted via SPSS 28.0 and SMART-PLS 4.0. The results revealed that self-efficacy significantly associates with happiness but not well-being, whereas resilience significantly associates with both happiness and well-being. Additionally, regular physical activity was found to moderate the relationships between self-efficacy and happiness, as well as between resilience and well-being. Notably, youth with hearing disabilities engaging in regular physical activity presented higher levels of self-efficacy, resilience, happiness, and well-being than did those not engaging in regular physical activity. The study emphasized the need to incorporate regular physical activity into the lives of young people with hearing disabilities to support their mental health and overall quality of life.